Two New Geraghty Type Contractions in Gb-Metric Spaces. (3rd February 2019) - Wang, Yixiao; Chen, Chunfang
Abstract : In this work, two Geraghty type contractions are introduced inG b -metric spaces, and some fixed point theorems about the contractions are proved. At the end of this article, a theorem about unique solution of an integral function is proved.